PENGARUH LITERASI KEUANGAN TERHADAP GAYA HIDUP KONSUMTIF DI KALANGAN PEKERJA - Ali Farhan (Media Mahardhika, 2020)
The study aims to test the influence between financial literacy and lifestyle on consumptive behaviour among workers, as well as to test the classic assumption in Keynes ' consumption theory, stating that consumption levels are affected by Income levels. This study was conducted using multiple regression tests that show the conclusion that financial literacy negatively affects the consumptive behaviour and lifestyle of positive effect on consumptive behavior, it contradicts With the classical theory of consumption caused this research is consistent with previous research among students (Pulungan and Febriaty, 2018; Lutfi and Herawati, 2015; Fauzia and Nurdin, 2019), consumption was not influenced by the level of income but also the level of financial literacy and lifestyle.